Updating the Aesthetic Fluency Scale: Revised long and short forms for research in the psychology of the arts. - Katherine N Cotter; Rebekah M Rodriguez-Boerwinkle; Alexander P Christensen; Anna Fekete; Jeffrey K Smith; Lisa F Smith; Pablo P L Tinio; Paul J Silvia (PLoS ONE, 2023)
People's knowledge about the arts shapes how they experience and engage with art. Since its introduction, the 10-item Aesthetic Fluency Scale has been widely used to measure self-reported art knowledge. Drawing from findings and researchers' experience since then, the present work develops and evaluates a Revised Aesthetic Fluency Scale using item response theory to broaden its scope (36 items) and refine its response scale. In a large sample (n = 2,089 English-speaking adults), Study 1 found strong evidence for unidimensionality, good item fit, and a difficulty level suitable for its targeted population; Study 2 (n = 392) provided initial evidence for score validity via relationships with art engagement, Openness to Experience, and aesthetic responsiveness; and Study 3 derived a brief, 10-item form for time-constrained projects. Taken together, the revised scales build upon lessons learned from the original and appear promising for the next generation of research.